International Business Strategy Formulation for the African Market of Copy Paper Company - Richiditya Hindami (Journal of Applied Business Administration, 2025)
This study examines strategic entry into the African market by a copy paper manufacturing company through internal and external business environment analysis. Using PESTEL, Porter’s Five Forces, SWOT, and VRIN frameworks, the research identifies key opportunities and risks. An Analytical Hierarchy Process (AHP) evaluates six strategic criteria: product standardization, pricing competitiveness, cost efficiency, regulatory compliance, adaptability, and cultural fit. Findings support a hybrid strategy combining transnational and multidomestic approaches to balance scale efficiency and local responsiveness. The study recommends phased market entry, regional partnerships, localized facilities, and improved market intelligence. These insights contribute to international business strategy by offering an evidence-based roadmap for firms targeting emerging markets in Africa.